Seawater carbonate chemistry and phytoplankton productivity and community structure in the coastal water of Southern East - Yukun Zhang; John Beardall; Kunshan Gao (PANGAEA, 2025)
In this study, we investigated the impacts of ocean acidification and warming on the phytoplankton community and primary productivity in the southern coastal water of the East China Sea by running land-based mesocosms controlled under current atmospheric pCO2 (430 μatm) and projected levels for the year 2100 (1000 μatm, HC, High CO2) at 27°C (ambient) and 30°C (warming, HT, High Temperature). This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were provided by the author of the related paper (see Related to) to the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-09-23.